Implementasi Sistem Bagi Hasil Mudharabah pada Koperasi Serba Usaha Amanah Desa Bunobogu Kecamatan Bunobogu Kabupaten Buol - Abdul Latif (Al-Buhuts, 2017)
This study aims to determine the system for the results of Mudharabah on Business Multipurpose Cooperative (KSU) Amanah Desa Bunobogu with Qualitative Descriptive Analysis method. This study uses primary data sources and secondary data relating to the annual revenue sharing system Mudharabah (2010-2014). The results of this study indicate that the profit sharing system is implemented by the Multipurpose Business Cooperative (KSU) Amanah Desa Bunobogu in the form of Mudharabah financing. With a guarantee statement on the process akadnya. In the event of negligence made by members who resulted in his business losing the goods made in the guarantee will be seized by the cooperative. Businesses that are established by members are mostly small and medium enterprises so often encountered bookkeeping that is not clear and just make a budget booklet at random. However, it does not become alaasan and hamper the growth of cooperatives which each year has increased the remaining results of operations. Unclear budget bookkeeping can result in member earnings manipulation, by lowering the profits earned and the effect on the revenue share installments